Modifikasi Coating Pada Permukaan Implan Ti-6Al-4VELI Berbasis Kombinasi Hidroksiapatit Cangkang Rajungan dan Polycaprolactone - Nibras, Adinda Lulyta Naifa; Susanti, Ajeng; Ramadhan, Haykal Nur Fajri; Kamilah, Villia Lidzati; Ningrum, Eva Oktavia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Ti-6Al-4V ELI (Extra Low Interstitials) is widely used material in orthopedics with its excellent mechanical properties and biocompatibility. However, in application it has a risk of corrosion caused by body fluids exposure as a results in inhibitation of tissue growth. Therefore, in this study modification of the surface of the Ti-6Al-4V ELI implan by coating Hydroxyapatite (HAp) combined with Polycaprolactone (PCL) using the dip coating method was carried out. The effect of HAp/PCL coating on implant morphology is investigated. Moreover, the effects of HAp/PCL concentrations on surface roughness, corrosion rates, and coating thickness are elucidated. The results showed that the hydroxyapatite of crab shells synthesized in a compliance with Food and Drug Association standards, i.e., Ca content of 93.03%. The functional groups confirmed with HAp standard chart JCPDS no. 09-0432 with crystallinity of 88.32%. The post-coated implant showed the coating thickness range of 140-200 µm and roughness average of 120-129 nm. In addition, the corrosion rate showed 0,043-0,33 mmpy which also complied with medical standard.